Strategi Pengelolaan Kebijakan untuk Meningkatkan Pelayanan pada Masyarakat Kota Bengkulu - Meysha Ananda Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The This research aims to determine and describe policy management strategies to improve public services, with a focus on community participation and policy evaluation. Increasing public expectations for fast, transparent and efficient services encourages the government to develop adaptive and innovative policies. This study uses qualitative methods to explore policy implementation in various regions. The research results show that the use of information technology has accelerated the service process and increased transparency, even though there are challenges with infrastructure gaps in several areas. In addition, active community participation in the policy-making process contributes to increasing the legitimacy and effectiveness of the policies implemented. However, unstructured policy evaluation is still an obstacle in assessing the success of public service programs. Therefore, it is important for the government to continue to innovate and adapt policies based on global changes, such as pandemics and environmental issues, to ensure more responsive and relevant public services in the future.